Abdominal aortic aneurysms that have ruptured or are at imminent risk of rupture - Corrêa,Ingrid Braga (2019)
Abstract The rupture of an abdominal aortic aneurysm (AAA) is considered a high-risk surgical emergency, given the catastrophic consequences and high mortality rate. The objective of this pictorial essay is to illustrate the radiological signs that indicate rupture or imminent rupture. To that end, we describe cases treated at our facility and present a brief review of the literature on the topic. The clinical diagnosis of imminent AAA rupture can be difficult, because patients are usually asymptomatic or have nonspecific pain complaints. In the subsequent follow-up, it is possible to identify radiological signs that indicate instability or rupture itself and thus change the prognosis. Computed tomography is the modality of choice for evaluating an AAA and abdominal pain in the emergency setting. It is therefore essential that the radiologist immediately identify the imaging findings that indicate AAA rupture or the imminent risk of such rupture.